COMPONENTS OF POLITICAL STABILITY IN SOCIETY TRANSFORMATION - Шаповаленко, М.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The trust is the main power legitimating factor that influens on transformation society. . The signs of constructive stability are considered and the factors that lead to the instability of the political system are identified The essence of cause-effectrelations between the level of public confidence and variousmechanisms of political power legitimization is described in Ukraine.